Bone turnover across the menopause transition The role of gonadal inhibins - Nicks, Kristy M. (2010)
Accumulating evidence demonstrates increasing bone turnover and bone loss in women prior to menopause and decreases in serum estradiol levels. Increased follicle-stimulating hormone levels have been correlated with some of these peri-menopausal changes. However, decreases in gonadal inhibins of the transforming growth factor (TGF)-β superfamily strongly correlate with increases in bone formation and resorption markers across the menopause transition and predict lumbar bone mass in peri-menopausal women, likely as a result of direct inhibin suppression of osteoblastogenesis and osteoclastogenesis. Inhibins bind specifically to cells during osteoblastogenesis and osteoclastogenesis. They can block bone morphogenetic protein (BMP)-stimulated osteoblast and osteoclast development as well as BMP-stimulated SMAD1 phosphorylation, likely via inhibin–β-glycan sequestration of BMP Type II receptor (BMPRII). Interestingly, continuous in vivo exposure to inhibin A is anabolic and protective against gonadectomyinduced bone loss in mice, suggesting that inhibins contribute to the endocrine regulation of bone metabolism via a bimodalmechanism of action whereby cycling inhibin exposure suppresses bone turnover and continuous exposure to inhibins is anabolic.